2011
DOI: 10.1177/1040638711407898
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cytochalasin D and abciximab on hemostasis in canine whole blood assessed by thromboelastography and the PFA-100® platelet function analyzer system

Abstract: Abstract. The selective inhibition of platelet function in whole blood coagulation testing may allow insights into the nature of hypercoagulability in dogs with critical illness. To determine the effects of cytochalasin D and abciximab on hemostatic parameters in canine citrated whole blood, an in-vitro study was designed using thromboelastography (TEG) and a platelet function analyzer (PFA-100®). 8 clinically healthy mixed breed dogs donated blood that was anticoagulated with 3.2% sodium citrate in a 9:1 bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…Platelet function recovers within three and a half hours of administration (Kageyama et al, 2001). In vitro, incubation of canine blood with abciximab prolongs PFA-100 â closure times (ADP-collagen cartridge) without significantly affecting thromboelastography (Brainard et al, 2011). In cats, a single study has evaluated abciximab in an arterial injury model, and demonstrated that a combination of aspirin and abciximab (0.25 mg/kg by intravenous bolus followed by an infusion of 0.125 lgÁkg/min) was more effective at inhibiting platelet function and preventing thrombus formation than aspirin alone.…”
Section: Gpiib/iiia Receptor Antagonistsmentioning
confidence: 99%
“…Platelet function recovers within three and a half hours of administration (Kageyama et al, 2001). In vitro, incubation of canine blood with abciximab prolongs PFA-100 â closure times (ADP-collagen cartridge) without significantly affecting thromboelastography (Brainard et al, 2011). In cats, a single study has evaluated abciximab in an arterial injury model, and demonstrated that a combination of aspirin and abciximab (0.25 mg/kg by intravenous bolus followed by an infusion of 0.125 lgÁkg/min) was more effective at inhibiting platelet function and preventing thrombus formation than aspirin alone.…”
Section: Gpiib/iiia Receptor Antagonistsmentioning
confidence: 99%
“…, Brainard et al . ). A citrated blood sample is added to a small cup (where activators of coagulation may or may not be added depending on the type of analysis to be performed), in which a pin is suspended. With TEG, the cup rotates which detects changes in torque of blood as a blood clot forms in the cup.…”
Section: Specific Tests Of Platelet Functionmentioning
confidence: 97%
“…, Brainard et al . ). TEG with “platelet mapping” can better assess platelet function, which requires two TEG machines running concurrently with different activators including heparin, which can exclude the contribution of thrombin to maximum clot strength. (Craft et al .…”
Section: Specific Tests Of Platelet Functionmentioning
confidence: 97%
“…A recent study examined the in vitro effect of the fungal metabolite cytochalasin D and the monoclonal α IIb β 3 antibody abciximab on TEG analyses. The results showed that cytochalasin, but not abciximab changed TEG tracings . These studies emphasize a unique feature of the TEG assay, which suggests that for selected drugs, it could be utilized in targeting therapy of the patient toward a normalization of the patients TEG tracings and hereby tailor dosage to meet the requirement of the individual patient.…”
Section: Diagnosis Of Hyperactive Plateletsmentioning
confidence: 99%